AN ANALYSIS OF INTERROGATIVE SENTENCES IN NOVEL “THE OLD MAN AND THE SEA” into the Indonesian Language - Yuni Haryati Aritonang; Yokhebed Tampone (STKIP PGRI Jombang, 2022)
This research is an attempt to describe and analyze English and Indonesian focused on interrogative sentences of the novel “The Old Man and The Sea” by considering the similarities and differences in the shape and function of sentences in both languages. This research, including research on the translation and accuracy of English question sentences to Indonesian. This research aims to (1) to find out the differences and similarities between the form and function of the question sentence in English and the form and function of the question sentence in Indonesian, (2) To find out the results of the analysis of question sentences according to the “QUASM” pattern and (3) to find out the types of question sentences from the novel above. The research method used is qualitatively descriptive. Data was collected from English novels and their Indonesian translations. The number of question sentence data is 99 sentences of which only 24 sentences correspond to the structure and components of “QUASM”. In English the question word has 3 forms, namely: yes/ no question, tag question, and wh-question while in Indonesian only have one form that is to uses the question words what, who, when, why, where, and how. The results of the data analysis showed that not all question sentences in English have the right translation when viewed from the Indonesian translation. Some translations of question sentences in English novels are seen in Indonesian novels will be turned into statement sentences and otherwise